Macroinvertebrates as a Bioindicator of Water Quality in the Jangkok River, Lombok Island - Nurhairani, Nurhairani; Candri, Dining Aidil; Zamroni, Yuliadi (Jurnal Pijar Mipa, 2024)
Rivers are water bodies in open ecosystems where activities in the environment have an impact on river water quality. Monitoring of water quality is necessary to preserve aquatic resources. One of the river basins on Lombok Island is the Jangkok River. This river has a high utility, so water quality monitoring is needed. Macroinvertebrates are one of the best biological indicators for water quality monitoring. The objective of this study is to determine the diversity of macroinvertebrates and the quality of Jangkok River waters by using macroinvertebrates as bioindicators so that the results of this study can be used as a reference basis for the future use of Jangkok River water in the allocation of community needs. The method used in this research is biomonitoring with macroinvertebrate bioindicators, and the technique used in sampling is purposive sampling. Sampling was conducted at three stations, namely the upstream, middle, and downstream parts of the Jangkok River. The data analysis used was the Family Biotic Index (FBI) supported by physical-chemical parameters. The results of this study showed that the macroinvertebrates identified were 721 individuals consisting of 5 classes, 17 orders, and 36 families. The water quality of the Jangkok River, based on the FBI value in the upstream and middle sections, is still included in the good category, while in the downstream section, it falls into the very bad category.